How to collaborate for health throughout the project timeline - a longitudinal study reflecting on implemented strategies in three projects for a healthy living environment - N. J. E. van Vooren; L. M. S. Janssen; H. W. Drewes; C. A. Baan; I. M. B. Bongers (BMC, 2023)
Abstract Background When improving the health of local and regional populations, cross-sector collaboration between different policy domains, non-governmental organisations and citizens themselves is needed. Previously, enabling factors and strategies have been identified to improve cross-sector collaboration for health. However, few longitudinal studies have been conducted to understand how the implementation of strategies for cross-sector collaboration changes throughout the collaboration process. The aim of this study is therefore to learn more about the different strategies that were implemented throughout three cross-sector collaboration projects for a healthy living environment. Methods The realist evaluation approach was used to understand how the implemented strategies worked, in which context, why and with what outcomes. Project partners were asked to reflect on their implemented strategies at two different moments in the project timelines, and quarterly updates with project leaders were held. In addition two reference panels were organised for data triangulation. Results Three key insights for successful cross-sector collaboration throughout projects for a healthy living environment were identified, namely 1. Investing in trust among the partners and faith in the project has a positive influence on continuing the collaboration throughout the project; 2. Making stakeholders actively participate throughout the project requires additional strategies after the onset of the project, and 3. Defining roles, tasks, and other prerequisites at the start of the project helps in pursuing the project over time, but needs re-examination throughout the project. These key insights were based on multiple examples of implemented strategies, linked to context, mechanisms and outcomes. Conclusions This study shows the different strategies that can be employed as the collaboration in projects for a healthy living environment progresses. We found that 'trust' does not merely include the relationships built between the partners, but at the onset of projects can also be based on faith in the project itself. In addition, as it can be difficult to foresee the right investments and strategies at the onset of the project, frequent reflection moments to choose fitting strategies might benefit regional partners in their cross-sector collaboration for health.